Epithelial-mesenchymal transition can suppress major attributes of human epithelial tumor-initiating cells - Celia-Terrassa, Toni; Meca-Cortes, Oscar; Mateo, Francesca; De Paz, Alexia Martinez; Rubio, Nuria; Arnal-Estape, Anna; Ell, Brian J; Bermudo, Raquel; Diaz, Alba; Guerra-Rebollo, Marta; Lozano, Juan Jose; Estaras, Conchi; et al. (The Journal of clinical investigation, 2012)
Malignant progression in cancer requires populations of tumor-initiating cells (TICs) endowed with unlimited self renewal, survival under stress, and establishment of distant metastases. Additionally, the acquisition of invasive properties driven by epithelial-mesenchymal transition (EMT) is critical for the evolution of neoplastic cells into fully metastatic populations. Here, we characterize 2 human cellular models derived from prostate and bladder cancer cell lines to better understand the relationship between TIC and EMT programs in local invasiveness and distant metastasis. The model tumor subpopulations that expressed a strong epithelial gene program were enriched in highly metastatic TICs, while a second subpopulation with stable mesenchymal traits was impoverished in TICs. Constitutive overexpression of the transcription factor Snai1 in the epithelial/TIC-enriched populations engaged a mesenchymal gene program and suppressed their self renewal and metastatic phenotypes. Conversely, knockdown of EMT factors in the mesenchymal-like prostate cancer cell subpopulation caused a gain in epithelial features and properties of TICs. Both tumor cell subpopulations cooperated so that the nonmetastatic mesenchymal-like prostate cancer subpopulation enhanced the in vitro invasiveness of the metastatic epithelial subpopulation and, in vivo, promoted the escape of the latter from primary implantation sites and accelerated their metastatic colonization. Our models provide new insights into how dynamic interactions among epithelial, self-renewal, and mesenchymal gene programs determine the plasticity of epithelial TICs.